2022
DOI: 10.1177/20539517221089310
|View full text |Cite
|
Sign up to set email alerts
|

Datafication and the practice of intelligence production

Abstract: Datafication of social life affects what society regards as knowledge. Jasanoff’s regimes of sight framework provides three ideal-type models of authorised knowing in environmental data practice. This paper applies Jasanoff's framework for analysing intelligence practice through an exploratory empirical study of crime and intelligence practitioners in a selection of police services in Australia, New Zealand, Canada and the United States. The paper argues that the ‘view from somewhere’ (VFS) captures the essenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The study by Neiva and colleagues (2022) also found that police professionals’ cooperation in the EU showed promising expectations about the role of Big Data in criminal investigations by making use of DNA databases; namely, in terms of its perceived capability to advance cold criminal cases and strengthen the interoperability of multiple data sets in ways that produce intelligence valuable for criminal investigations. Chan and colleagues (2022) draw similar conclusions: the interoperability of databases enhanced by the integration of technological platforms was conceived by the police professionals as an upgrade to their work. Participants’ views were focused on the benefits of Big Data in improving their intelligence work given its capabilities to enhance access, storage, analysis and sharing of different data.…”
Section: Resultssupporting
confidence: 52%
See 4 more Smart Citations
“…The study by Neiva and colleagues (2022) also found that police professionals’ cooperation in the EU showed promising expectations about the role of Big Data in criminal investigations by making use of DNA databases; namely, in terms of its perceived capability to advance cold criminal cases and strengthen the interoperability of multiple data sets in ways that produce intelligence valuable for criminal investigations. Chan and colleagues (2022) draw similar conclusions: the interoperability of databases enhanced by the integration of technological platforms was conceived by the police professionals as an upgrade to their work. Participants’ views were focused on the benefits of Big Data in improving their intelligence work given its capabilities to enhance access, storage, analysis and sharing of different data.…”
Section: Resultssupporting
confidence: 52%
“…The studies were published between 2015 (Sanders et al, 2015) and 2022 (Chan et al, 2022; Neiva et al, 2022; Simmler et al, 2022). Ten of the fourteen studies were conducted in a single country, namely the United Kingdom (Dencik et al, 2018; Fussey and Sandhu, 2020; Sandhu and Fussey, 2021), Canada (Sanders et al, 2015; Sanders and Condon, 2017), the United States (Brayne, 2017; Brayne and Christin, 2020), Colombia (Barreneche, 2019), Australia (Chan and Moses, 2017), and Switzerland (Simmler et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations